2022
DOI: 10.1007/s10708-022-10811-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the shared working spaces: a Geography of Co-working supply in Delhi

Abstract: The present paper investigates the location pattern of co-working spaces in Delhi which is absent in the existing body of knowledge. Delhi is a political, administrative, educational, scientific and innovation capital that accommodates many co-working spaces in India. We developed Ordinary least squares (OLS) and geographically weighted regression (GWR) models to understand the associations of co-working spaces of digital labourers with other urban socio-economic, services and lifestyle variables in Delhi usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
2
0
1
Order By: Relevance
“…It has been demonstrated that small businesses and self-employed individuals can enhance their well-being and enjoy economic benefits thanks to co-working [47,48]. The same model can apply to artisans who want to share a workshop space, allowing them to share the cost of infrastructure and other bills while also exchanging ideas and practices.…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that small businesses and self-employed individuals can enhance their well-being and enjoy economic benefits thanks to co-working [47,48]. The same model can apply to artisans who want to share a workshop space, allowing them to share the cost of infrastructure and other bills while also exchanging ideas and practices.…”
Section: Discussionmentioning
confidence: 98%
“…Un d'ells és l'accessibilitat, que fa referència a la facilitat de desplaçament i mobilitat entre el lloc de treball i la resta de la ciutat. Sovint, els espais de cotreball es troben en zones cèntriques o ben comunicades per transport públic o privat, amb l'objectiu d'atraure a un major nombre possible clientela i oferir-los comoditat i flexibilitat, com s'ha observat diverses ciutats com Hèlsinki (Di Marí et al, 2018), Roma (Fiorentino, 2019) o altres parts del món com l'Índia (Tiwari, 2022).…”
Section: Factors De Localització Dels Espais De Cotreball a Les Ciutatsunclassified
“…A region's accessibility plays a crucial role in attracting potential coworking space users (Stam and van de Vrande 2017; Avdikos and Merkel 2020). In our paper, instead of proximity to metro stations, which is typically used in studies at the urban scale level (Mourad et al 2021;Tiwari 2022), we decided to include the presence of the largest airport as a proxy for the international and national transport accessibility that drives the emergence of newcomers and consequently coworking spaces to the area. Since isolated areas suffer from their remoteness, a dummy variable for island regions was introduced.…”
Section: Literature Reviewmentioning
confidence: 99%